Literature review: the efficacy of mobile learning media in enhancing critical thinking skills among elementary school students - Dewi, Tanti Agviola; Sumarti, Sri Susilogati; Ellianawati, Ellianawati; Subali, Bambang; Avrilianda, Decky (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The ongoing Industrial Revolution 4.0 is accompanied by the swift advancement of science and technology, necessitating high-quality Human Resources (HR). To do this, educational resources must be changed, particularly the media used for instruction. The educational sector currently requires practical and effective learning media, particularly through the utilization of mobile learning. This study aims to assess the efficacy of mobile learning media in enhancing critical thinking abilities among elementary school pupils. To examine the effectiveness of android-based learning media for improving critical thinking skills. The study used the Systematic Literature Review (SLR) methodology for its literature review component. The Systematic Literature Review method involves examining publications that align with the subject matter. This research is expected to improve future research on Android-based learning media. This study's findings indicate that mobile learning enhances critical thinking skills in elementary education. Research demonstrates that mobile learning media serves as an effective tool, particularly for fostering students' critical thinking abilities.